Talking Tax to Social Policy Historians - Pasolli, Lisa (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2021)
When it comes to the links between taxation and social policy, the growth of the welfare state, funded by income tax, is the obvious starting point. But in Give and Take, Tillotson goes far beyond the obvious. In her hands, the tax system has complex “welfare effects.” Looking through the tax lens, Tillotson gives us fresh perspectives on the origins, politics, and consequences of social welfare programs, as well as the negotiation of social citizenship rights and obligations. In this essay, I also suggest Give and Take points us towards a relatively unexplored set of questions about the history of social policy in twentieth-century Canada, namely how the tax system and especially tax expenditures have been used to achieve social policy objectives.